2013
DOI: 10.5267/j.msl.2013.04.003
|View full text |Cite
|
Sign up to set email alerts
|

A study on the effect of advertisements on customers' willingness to accept banking services based on modulatory role of brand: A case study of Bank Parsian

Abstract: During the past few years, there have been growing competition in banking industry in Iran and there is a growing trend on emerge of new banks, which makes it difficult for existing banks to keep market share. In this paper, we study the effect of advertisements on customers’ willingness to accept banking services based on modulatory role of brand. The proposed study has been performed among 440 randomly selected customers in city of Tehran, Iran who were doing banking business with one of Iranian banks called… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…They stated that their results could enhance the validity of the performance-only approach to service quality through the concentration on the multidimensional facets of the SERVPERF scale. Danaei et al (2013) studied the impact of advertisements on customers' willingness to accept banking services based on modulatory role of brand. They reported that there was a positive and meaningful relationship between brand advertisement and associate name and brand identification.…”
Section: Introductionmentioning
confidence: 99%
“…They stated that their results could enhance the validity of the performance-only approach to service quality through the concentration on the multidimensional facets of the SERVPERF scale. Danaei et al (2013) studied the impact of advertisements on customers' willingness to accept banking services based on modulatory role of brand. They reported that there was a positive and meaningful relationship between brand advertisement and associate name and brand identification.…”
Section: Introductionmentioning
confidence: 99%
“…They reported six major factors including brand loyalty, physical characteristics, pricing effects, performance characteristics, brand relationship and brand position influence food industry, significantly. Danaei et al (2013) studied the effect of advertisements on customers' willingness to accept banking services based on modulatory role of brand. They analyzed the gathered data using structural equation modeling and the preliminary results indicated that there was a positive and meaningful relationship between brand advertisement and associate name and brand identification.…”
Section: Introductionmentioning
confidence: 99%